2018
DOI: 10.1055/a-0577-4280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Intensity on Microvascular Function in Obese Adolescents

Abstract: The optimal exercise modality for the improvement of health-related parameters and microvascular function in obese adolescents is not yet fully understood. Therefore, this study aimed to 1) compare the microvascular phenotype of obese and normal-weight adolescents; and 2) to determine the effects of a lifestyle intervention including three months of moderate continuous training (MCT) or high-intensity interval training (HIIT) on health-related parameters and microvascular function in 29 obese adolescents. Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Study characteristics are presented as mean ± SD unless otherwise stated. Eighteen effects from 17 RCTs [11,12,13,14,15,16,18,19,20,21,22,23,24,25,26,27,28] of 563 participants were included in the review (Table 1). Of the 17 included studies, 10 enrolled obese subjects [11,12,13,16,20,21,23,26,27,28], 1 included normal weight and obese subjects [39], and 6 included normal weight subjects [14,18,19,22,24,25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics are presented as mean ± SD unless otherwise stated. Eighteen effects from 17 RCTs [11,12,13,14,15,16,18,19,20,21,22,23,24,25,26,27,28] of 563 participants were included in the review (Table 1). Of the 17 included studies, 10 enrolled obese subjects [11,12,13,16,20,21,23,26,27,28], 1 included normal weight and obese subjects [39], and 6 included normal weight subjects [14,18,19,22,24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen effects from 17 RCTs [11,12,13,14,15,16,18,19,20,21,22,23,24,25,26,27,28] of 563 participants were included in the review (Table 1). Of the 17 included studies, 10 enrolled obese subjects [11,12,13,16,20,21,23,26,27,28], 1 included normal weight and obese subjects [39], and 6 included normal weight subjects [14,18,19,22,24,25]. Five studies included boys only [13,18,23,25,27], 2 studies did not reported gender [15,22] and the 10 remaining studies included both boys and girls [11,12,14,16,19,20,21,24,26,28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-interval training programs consisted of training performed at intensities >90% VO 2peak or HR max for 30 s to 2 min intervals with 30 s to 1 min recovery (Corte de Araujo et al, 2012;Xiuming, 2014;Murphy et al, 2015;Lazzer et al, 2017). The long-interval training programs consisted of training performed at intensities of 80% VO 2peak or 85-100% HR max fort 2-4 min intervals with 1-3 min recovery (Koubaa et al, 2013;Starkoff et al, 2014;Mahgoub and Aly, 2015;Dias et al, 2018;Morrissey et al, 2018). The majority of the MICT programs consisted of training performed at 60-80% HR max or 60-70% VO 2peak for 30-40 min.…”
Section: Study Characteristics and Participantsmentioning
confidence: 99%
“…During the 3-month program, exercise training consisted in supervised moderate-to-vigorous intensity exercise for 180 min/week. Each session mostly involved aerobic exercise, including training circuit, boxing, basket-ball and Nordic walk, with alternating short periods of high-intensity exercise interspersed among periods of lower intensity, as previously described [20].…”
Section: Methodsmentioning
confidence: 99%